Celebrating Al and Rose Watkins' 35th Wedding Anniversary - Watkins, Howard::::::::: (1979)
Cliff Williamson, Rocco Daughter, Rose Watkins holding grandson Adam Watkins, Betty Williamson, Leffie Watkins